2003
DOI: 10.1071/ea01155
|View full text |Cite
|
Sign up to set email alerts
|

Lithium salts as a marker of intake of supplements by cattle

Abstract: Abstract. In a series of experiments the appearance of lithium cation in plasma following ingestion or intravenous administration of lithium salts was measured in order to examine the suitability of lithium as a marker of supplement intake by cattle. In experiment 1, cattle were offered low quality hay ad libitum and 0.15, 0.4, 1.0 and 3.0 kg cottonseed meal (CSM) supplement per day. Following ingestion of lithium-labelled CSM, the lithium concentration in plasma reached a maximum after about 24 h and the subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 27 publications
(36 reference statements)
1
7
0
Order By: Relevance
“…The high variation in the distribution among heifers of intakes of LMM supplements, and the substantial proportion of non-consumers of the LMM supplement on the day on which the lithium-labelled supplements were fed, observed in the present study are in agreement with previous reports of large variation among individuals and high proportions of nonconsumers in groups of cattle fed LMM (Dixon et al 2000(Dixon et al , 2001 or feed block supplements (Murray et al 1978;Eggington et al 1990;Dixon et al 2003b). The procedure using lithiumlabelled supplements to estimate the distribution in supplement intake among animals in herds has been validated, including for circumstances similar to the present study where animals were blood sampled~24 h after ingestion of lithium-labelled supplements (Dixon et al 2003a); larger errors may occur if there is a shorter interval between ingestion of the lithiumlabelled supplement and blood sampling (McLennan 1999). In addition, as the paddock groups of heifers in the present study were observed to behave as a single group, ingestion of the lithium-labelled supplement would have been over an interval much shorter than the 6 h during which the labelled supplement was offered.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The high variation in the distribution among heifers of intakes of LMM supplements, and the substantial proportion of non-consumers of the LMM supplement on the day on which the lithium-labelled supplements were fed, observed in the present study are in agreement with previous reports of large variation among individuals and high proportions of nonconsumers in groups of cattle fed LMM (Dixon et al 2000(Dixon et al , 2001 or feed block supplements (Murray et al 1978;Eggington et al 1990;Dixon et al 2003b). The procedure using lithiumlabelled supplements to estimate the distribution in supplement intake among animals in herds has been validated, including for circumstances similar to the present study where animals were blood sampled~24 h after ingestion of lithium-labelled supplements (Dixon et al 2003a); larger errors may occur if there is a shorter interval between ingestion of the lithiumlabelled supplement and blood sampling (McLennan 1999). In addition, as the paddock groups of heifers in the present study were observed to behave as a single group, ingestion of the lithium-labelled supplement would have been over an interval much shorter than the 6 h during which the labelled supplement was offered.…”
Section: Discussionsupporting
confidence: 91%
“…Following the procedures described by Suharyono (1992) and Dixon et al (2003a) lithium was used as a marker on two occasions to estimate the distribution of ingested supplement among individual heifers in each paddock group. Lithiumlabelled LMM supplements were prepared by mixing lithium sulfate monohydrate (6-12 g lithium/kg supplement) with the ingredients during preparation; the amount of lithium sulfate added was intended to provide~1.5 mg lithium/kg LW.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These recovery values are to be expected, as urinary Li concentration followed a curvilinear pattern in accordance with a marker approaching plateau concentration after long-term continuous infusion, and simply reflect the time of sampling in relation to marker kinetics of Li and its movement between pools such as the digestive tract and the plasma. Dixon et al (2003) found that the change in plasma lithium concentration over 96 h following intravenous injection was most adequately described by three exponential compartments. They hypothesised that the third compartment principally represented renal excretion, while the first and second compartments could have been associated with kinetic compartments in the extracellular fluid, rumen and post-ruminal digesta, and other body pools, or with mixing of lithium in these pools.…”
Section: Discussionmentioning
confidence: 99%
“…Chromium complexed with ethylenediamine tetra-acetic acid (CrEDTA; Downes and -Present address: Department of Primary Industries and Fisheries, PO Box 6014, CQMC, Rockhampton, QLD 4702, Australia. E-mail: maree.bowen@ dpi.qld.gov.au McDonald, 1964;Stacy and Thorburn, 1966) and lithium salts (Suharyono, 1992;Dixon et al, 2003) have been investigated for suitability as markers to examine such factors as the rate of flow and volume of rumen fluid, and the intake of supplements, by ruminants. The application of these substances as intravenously administered markers for estimating urine output in grazing ruminants requires knowledge of the recovery of the marker in the urine and of the diurnal variation in marker concentration, or the metabolite : marker ratio, in the urine.…”
Section: Introductionmentioning
confidence: 99%